Kinematics of the axial segment of horses submitted to dynamic mobilization exercises (Research, Society and Development, 2022)
This study aimed to investigate the kinematic effects of dynamic mobilization exercises on the axial segment in horses. Twelve horses crossbreed were used, which were monitored before (day 0) and at the end of the experimental period (day 120), distributed in an entirely randomized design, totalizing six repetitions per treatment The treatments consisted of two experimental groups, one composed of horses not performing the dynamic mobilization exercises and the other composed of horses submitted to the mobilization program. The static kinematic variables were evaluated, by means of hemispherical markers such as depth (cm), angle (°), difference in depth and angle, for each vertebral level analyzed (T10, T13, T17, L1 and L3), as well as total range of motion for depth and angle, in which this parameter expressed the thoracolumbar motion in its entirety. The performance of dynamic mobilization produced a significant (P